1965
DOI: 10.1149/1.2423404
|View full text |Cite
|
Sign up to set email alerts
|

An Electrode Mechanism for the Electrochemical Reduction of M-dinitrobenzene

Abstract: This is an integrated polarographic and potentiostatic study on the mechanism of the cathodic reduction of m‐dinitrobenzene for various pH values of aqueous electrolytes. The polarographic results confirmed previous results of a two‐stage reduction involving four electrons in each step. The supporting coulometric work was performed potentiostatically at a graphite cathode under a nitrogen atmosphere at a controlled potential of −0.48v on a solution of pH 6.00. The product of the first step, 3‐nitrophenylhydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1966
1966
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…It was reported that A7-nitroanabasine reduces to A'-hydroxylaminoanabasine and then to iV-aminoanabasine (836,837). A two-stage reduction of four electrons each with 3-nitrophenylhydroxylamine, the product of the first, and ?n-dihydroxylamine benzene, the product of the second was reported for m-dinitrobenzene (322). o-Dinitrobenzene was found to be reduced in strongly acidic solution to o-quinonediimine which rapidly converts to 2,3diaminophenazine and 2-hydroxy-3aminophenazine.…”
Section: Irreversible Systemsmentioning
confidence: 84%
See 1 more Smart Citation
“…It was reported that A7-nitroanabasine reduces to A'-hydroxylaminoanabasine and then to iV-aminoanabasine (836,837). A two-stage reduction of four electrons each with 3-nitrophenylhydroxylamine, the product of the first, and ?n-dihydroxylamine benzene, the product of the second was reported for m-dinitrobenzene (322). o-Dinitrobenzene was found to be reduced in strongly acidic solution to o-quinonediimine which rapidly converts to 2,3diaminophenazine and 2-hydroxy-3aminophenazine.…”
Section: Irreversible Systemsmentioning
confidence: 84%
“…A two-stage reduction of four electrons each with S-nitrophenylhydroxylamine, the product of the first, and m-dihydroxylamine benzene, the product of t'he second was reported for m-dinitrobenzene (322).…”
Section: Acids and Their Derivatives Ilmentioning
confidence: 98%
“…References to the hundreds of succeeding studies on nitro-reduction are available from the review on cathode reduction and standard compilations (1,111). The possible use of polynitrobenzenes as battery depolarizers has motivated still further study (3,46,47,52,53,62,87,113,116). However, many of these studies have taken place at potentially catalytically poisoning mercury electrodes.…”
Section: Electrogenerative Reduction Of Nitro Compoundsmentioning
confidence: 99%
“…(1) vermuten konnte. Bei pH-Werten > 2 wird das m-Dinitrobenzol in zwei nacheinander ablaufenden 4-Elektronenschritten reduziert [5], wobei zunlchst m-Nitrophenylhydroxylamin und dann das Phenylenhydroxylamin gebildet wird…”
Section: Einflub Des Ph-wertes Des Elektrolyten Auf Elektrodenpotentiunclassified